Comparison of human amniotic membrane decellularisation approaches for hESC-derived RPE cells culture. Issue 1 (6th September 2022) - Daniele, Elena; Ferrari, Barbara; Rassu, Nicolò; Ben-Nun, Joshua; Bosio, Lorenzo; Barbaro, Vanessa; Ferrari, Stefano; Ponzin, Diego
Abstract : Objective: Recent clinical studies have shown that the transplantation of functional retinal pigment epithelium (RPE) cells can prevent the onset of RPE degeneration in age-related macular degeneration. This study aimed to investigate the potential of human amniotic membrane (hAM) as a viable scaffold for the growth and proliferation of pluripotent-derived RPE cells. Methods and analysis: Three enzymatic hAM de-epithelialisation methods (thermolysin, trypsin-EDTA and dispase II) were assessed by histological analysis and optical coherence tomography (OCT). We generated RPE cells from a human embryonic stem cell (hESC) line subjected to spontaneous differentiation in feeder-free conditions. The hESC-derived RPE cells were seeded over denuded hAM at a density of 2.0×10 5 cells/cm 2 and maintained in culture for up to 4 weeks. Immnofluorescence was carried out to evaluate the development of a confluent monolayer of RPE cells on the top of the hAM. Conditioned medium was collected to measure pigment epithelium-derived factor (PEDF) concentration by ELISA. Results: Laminin α5 and collagen IV staining confirmed the efficiency of the de-epithelialisation process. In particular, thermolysin showed good retention of tissue integrity on OCT images and greater preservation of the hAM basement membrane. The hESC-derived RPE cells formed patches of pigmented cells interspersed along the denuded hAM, but failed to form a regular sheet of RPE cells. These cells expressed typical RPE markers, such as PMEL17 and RPE65, but they secreted low levels of PEDF. Conclusion: The biological variability of the hAM could influence the adhesion and the expansion of hESC-derived RPE cells. Further studies are required to verify whether a non-confluent monolayer might represent a limit to transplantation.